Pengaruh asimetri informasi, corporate governance terhadap earning management pada perusahaan BUMN di Indonesia - Puji Nurhayati; Heidy Paramitha Devi; Amelia Marifatul Azizah (Politeknik Ganesha Medan, 2022)
Financial statements are one of the sources of information used to assess the company's financial position and performance. Policies and decisions taken in the process of preparing financial statements will affect the assessment of the company's performance. The choice of accounting policy that management deliberately carried out for profit reporting purposes is called Earnings management. Earnings management is a difficult phenomenon to avoid due to the impact of accruals in the preparation of financial statements. The agency's theory provides the view that earnings management problems can be minimized through corporate governance. The purpose of this research is to provide empirical evidence by analyzing the influence of information asymmetry, the proportion of independent commissioners and the size of the board of commissioners on earnings management of SOEs companies in Indonesia during 2016-2018. Sampling techniques using purposive sampling, obtained 99 sample of STATE-owned enterprises in Indonesia . Data analysis techniques use data regression analysis panel e-views program 9. The data analysis tool uses the Random Effect Model (REM) analysis model. The results showed that the asymmetry of information, the proportion of independent board of commissioners and the size of the board of commissioners did not significantly affect earnings management of STATE-owned enterprises in Indonesia. Keywords: Information Asymmetry, Proportion of Independent Board of Commissioners, Size Of Board of Commissioners, Earnings Management Financial statements are one of the sources of information used to assess the company's financial position and performance. Policies and decisions taken in the process of preparing financial statements will affect the assessment of the company's performance. The choice of accounting policy that management deliberately carried out for profit reporting purposes is called Earnings management. Earnings management is a difficult phenomenon to avoid due to the impact of accruals in the preparation of financial statements. The agency's theory provides the view that earnings management problems can be minimized through corporate governance. The purpose of this research is to provide empirical evidence by analyzing the influence of information asymmetry, the proportion of independent commissioners and the size of the board of commissioners on earnings management of SOEs companies in Indonesia during 2016-2018. Sampling techniques using purposive sampling, obtained 99 sample of STATE-owned enterprises in Indonesia . Data analysis techniques use data regression analysis panel e-views program 9. The data analysis tool uses the Random Effect Model (REM) analysis model. The results showed that the asymmetry of information, the proportion of independent board of commissioners and the size of the board of commissioners did not significantly affect earnings management of STATE-owned enterprises in Indonesia. Keywords: Information Asymmetry, Proportion of Independent Board of Commissioners, Size Of Board of Commissioners, Earnings Management